2017
DOI: 10.1021/acs.organomet.7b00158
|View full text |Cite
|
Sign up to set email alerts
|

Convergent (De)Hydrogenative Pathways via a Rhodium α-Hydroxylalkyl Complex

Abstract: We report the convergent reaction pathways between [RhH(PPh 3) 4 ] and POP ketone (1) and alcohol (2) ligands that terminate in the formation of an α-hydroxylalkyl rhodium(I) complex (3), representing two halves of a formal reduction/oxidation pathway between 1 and 2. In the case of hydride transfer to 1, the formation of the α-hydroxylalkyl rhodium(I) complex (3) proceeds via a rare hydrido(η 2carbonyl) complex (4). C−H activation in 2 at the proligand's central methine position, rather than O−H activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…Possible reactivity involving the ketone moiety include: a) hemilabile behavior upon changing the oxidation state of the metal center, b) reversible addition of hydride to the moiety under catalytic conditions in analogy to the borane in Peters' catalyst, or c) its hydrosilylation to generate a catalytically active species. Recent experimental and computational investigations on similar Ph dpbp complexes with Co or Rh by Young and co‐workers showed the ability of the ketone to reversibly accept a hydride equivalent to become an sp 3 hydroxyalkyl ligand , . Related processes are plausible under hydrosilylation conditions, but the exact nature of the involved species is unclear, and further investigations are ongoing to address details of the mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Possible reactivity involving the ketone moiety include: a) hemilabile behavior upon changing the oxidation state of the metal center, b) reversible addition of hydride to the moiety under catalytic conditions in analogy to the borane in Peters' catalyst, or c) its hydrosilylation to generate a catalytically active species. Recent experimental and computational investigations on similar Ph dpbp complexes with Co or Rh by Young and co‐workers showed the ability of the ketone to reversibly accept a hydride equivalent to become an sp 3 hydroxyalkyl ligand , . Related processes are plausible under hydrosilylation conditions, but the exact nature of the involved species is unclear, and further investigations are ongoing to address details of the mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Recently while exploring the mechanism of transfer hydrogenation mediated by acidic rhodium hydrides, 20 we realized that facile access to PC carbene P systems could be achieved directly via dehydration of PCP α-hydroxyalkyl ligands. 18 , 19 As such ligands can be generated by carbonyl insertion into metal hydrides, C–H activation of the proligand can be avoided completely.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation spectroscopy revealed a 13 C resonance at δ C =106.2 (t, 2 J PC =11.0 Hz) arising from the central alkyl carbon donor atom. α‐Hydroxyalkyl ligands are kinetically unstable but have previously been shown to be accessible from both alcohol and ketone precursors [22] …”
Section: Resultsmentioning
confidence: 99%
“…a-Hydroxyalkyl ligands are kinetically unstable but have previously been shown to be accessible from both alcohol and ketone precursors. [22] Overtime,c ompound 3 eliminates either hydrogen to generate compound 4 or water to generate the desired product, PC carbene Pc omplex 1 (Scheme 1). It was observed that the presence of as trong,n on-nucleophilic base (e.g.…”
Section: Resultsmentioning
confidence: 99%